Extra‐articular resection for bone sarcomas involving the hip joint. Issue 2 (19th November 2019) - Fujiwara, Tomohiro; Tsuda, Yusuke; Evans, Scott; Stevenson, Jonathan; Parry, Michael; Jeys, Lee; Abudu, Adesegun
Abstract: Aim: The aim of this study was to determine the oncologic, functional, and clinical outcomes after the extra‐articular resection and limb‐salvage reconstruction of the hip joint. Methods: A retrospective study of 34 patients who underwent extra‐articular resection of the hip joint for bone sarcomas between 1996 and 2016 was conducted. The primary tumor site was pelvis in 26 patients (76%) and femur in eight (24%). Results: The surgical margins achieved were clear in 31 (91%) patients, and seven (21%) patients developed local recurrence; mostly occurring in pelvic tumors (n = 6). The 3‐year overall survival was 63% with a median follow‐up of 38 months (range, 5‐219), which showed no statistical difference in tumor location. The most common complication was deep infection (n = 7) and dislocation (n = 7), mostly seen in pelvic tumors. Implant failure was seen in two patients with pelvic tumors, while no failure was noted in patients with femoral tumors. The median Musculoskeletal Tumour Society score was 69%; 67% for pelvic tumors and 73% for femoral tumors ( P = .535). Conclusion: Despite complex surgery, extra‐articular resection of the hip joint can achieve oncologically and functionally acceptable outcomes. While tumors of the pelvis are associated with a higher incidence of infection and local recurrence after resection, resection of tumors involving the femur are well tolerated.